Necessary Fictions - Croft, Barbara (Book collections on Project MUSE., 1998)
A collection of stories on how people handle failure and wrong decisions. In one, a draft dodger from the Vietnam War tries to make up for fleeing the country by working as an orderly in a veterans' hospital, while in another a carpenter commits suicide when he fails to build the perfect house.